VD_FINDINFO Jug / 2016 / 182 vom 29. Oktober 2015 - VD Tribunal cantonal (2015)
ACTE D'ORDRE SEXUEL AVEC UN ENFANT, APPRÉCIATION DES PREUVES, TORT MORAL | 187 ch. 1 CP, 47 CP, 97 al. 2 CP, 97 al. 4 CP, 10 CPP (CH)